Quantitative Trait Loci Mapping and Candidate Gene Analysis of Low Temperature Tolerance in Cucumber Seedlings - Dong, Shaoyun; Wang, Weiping; Bo, Kailiang; Miao, Han; Song, Zichao; Wei, Shuang; Zhang, Shengping; Gu, Xingfang (Frontiers in Plant Science, 2019)
Cucumber (Cucumis sativus L.) is an economically important vegetable crop worldwide, but it is sensitive to low temperatures. Cucumber seedlings exposed to long-term low temperature stress (LT), i.e. below 20 °C during the day, and 8 °C at night, exhibit leaf yellowing, accelerated senescence, and reduced yield, therefore posing a threat to cucumber production. Studying the underlying mechanisms involved in LT tolerance in cucumber seedlings, and developing germplasm with improved LT-tolerance could provide fundamental solutions to the problem. In this study, an F2 population was generated from two parental lines, 'CG104' (LT-tolerant inbred line) and 'CG37' (LT-sensitive inbred line), to identify loci that are responsible for LT tolerance in cucumber seedlings. Replicated phenotypic analysis of the F2-derived F3 family using a low-temperature injury index (LTII) suggested that the LT tolerance of cucumber seedlings is controlled by multiple genes. A genetic map of 990.8 cM was constructed, with an average interval between markers of 5.2 cM. One Quantitative Trait Loci (QTL) named qLTT5.1 on chromosome 5, and two QTLs named qLTT6.1 and qLTT6.2 on chromosome 6 were detected. Among them, qLTT6.2 accounted for 26.8% and 24.1% of the phenotypic variation in two different experiments. SNP variations within the region of qLTT6.2 were analyzed using two contrasting in silico bulks generated from the cucumber core germplasm. Result showed that 214 SNPs were distributed within the 42-kb interval, containing three candidate genes. Real-time quantitative reverse transcription PCR and sequence analysis suggested that two genes Csa6G445210, an auxin response factor, and Csa6G445230, an ethylene-responsive transmembrane protein, might be candidate genes responsible for LT tolerance in cucumber seedlings. This study furthers the understanding of the molecular mechanism underlying LT tolerance in cucumber seedlings, and provides new markers for molecular breeding.